2019
DOI: 10.1186/s13569-019-0115-4
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of finding new therapeutic avenues in soft tissue sarcomas

Abstract: Soft tissue sarcomas are rare malignancies of mesenchymal origin comprising about 1% of all adult cancers. Systemic therapies for locally advanced and metastatic disease have been restricted for decades to very few effective and approved agents such as doxorubicin and ifosfamide. However, new therapeutic avenues including new drug developments and registrations such as trabectedin, pazopanib and eribulin as well as numerous clinical trial options have recently enriched the therapeutic armamentarium in the trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Single-agent doxorubicin, introduced in the early 1970s, remains the standard treatment option for many patients with metastatic STS [4,5]. Several randomized trials have failed to show any survival benefit for combination therapies of doxorubicin and novel agents compared with single-agent doxorubicin [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Single-agent doxorubicin, introduced in the early 1970s, remains the standard treatment option for many patients with metastatic STS [4,5]. Several randomized trials have failed to show any survival benefit for combination therapies of doxorubicin and novel agents compared with single-agent doxorubicin [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…For leiomyosarcoma, doxorubicin and dacarbazine could be considered, instead of anthracyclines plus ifosfamide, since this latter could be even detrimental in this specific subtype according to retrospective comparisons. [IV, B] [38]. The combination of gemcitabine plus docetaxel is not recommended as a first-line option for the treatment of advanced STS [39].…”
Section: Management Of Advanced/metastatic Diseasementioning
confidence: 99%
“…Systemic therapy options vary according to histologic subtype and include cytotoxic chemotherapies (doxorubicin and/or ifosfamide-based regimens), anti-angiogenic multikinase inhibitors (such as pazopanib, regorafenib, sunitinib, and cabozantinib), and multikinase inhibitors that target NTRK, ROS1, and ALK (entrectinib). 3,8,[20][21][22] Despite the availability of multiple treatment options, there remains an unmet need for effective targeted treatments.…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
“…However, no statistically significant OS benefit could be demonstrated by the addition of other chemotherapy to doxorubicin. 8 Moreover, a recent partitioned survival modeling study that estimated the long-term comparative effectiveness of larotrectinib and standard of care in adult patients with STS showed that patients receiving larotrectinib gained 5.56 additional life years and 1.99 quality-adjusted life years compared with doxorubicin/ifosfamide. 23 Pazopanib, indicated for the treatment of adults with advanced STS, 24 demonstrated an ORR of 9%, median PFS of 4.6 months, and OS of 12.5 months in a phase 3 trial.…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
See 1 more Smart Citation